Cognitive Assessment Using the Anates Application on Solar System Material for Grade 6 Students of Karangkandri 04 Elementary School - Bety Andriyani; Subuh Anggoro (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to analyze the cognitive abilities of 6th grade students of Karangkandri 04 Elementary School in understanding solar system material using the Anates application as an evaluation tool. The instrument used was 10 multiple-choice questions arranged based on three cognitive levels in Bloom's Taxonomy, namely C1 (Remembering), C2 (Understanding), and C3 (Applying). This research method is quantitative descriptive, with data analysis techniques using Anates software to determine the level of difficulty, distinguishing power, and reliability of the questions.The results of the study showed that the highest level of student achievement was in the C1 realm (90%), then C2 (70%), and the lowest in C3 (50%). The Anates application helps in identifying less effective questions and provides a comprehensive picture of the quality of the evaluation instrument. The conclusion of this study is that students' basic understanding of the solar system material is quite good, but the ability to apply concepts still needs to be improved. The use of the Anates application has been proven to help teachers in compiling and analyzing questions that are of higher quality and in accordance with learning objectives.